Forecasting Price of Sorghum in Ajmer Market of Rajasthan : An Empirical Study - Sharma, Hemant; Burark, S.S. (Annals of Agricultural Research, 2016)
Sorghum is the most important food and fodder crop of dry land agriculture. Sorghum grains are important as food and livestock feed. This paper forecasts the future prices of sorghum from July 2012 to December 2012 based on secondary data from January 2002 to June 2012, as the forecasted commodity price plays an important role in taking any economic decision for a country. To forecast the sorghum price the various forms of ARIMA (Box-Jenkins model), Artificial Neural Network (ANN) and Exponential Smoothing models (Single, Double and Triple) were employed to predict the future prices in Ajmer market. ARIMA (1,1,2) Â model was the preferred model for forecasting sorghum price due to minimum value of Â MAD (44.92), MSE (4931.37) and MAPE (3.15) when compared to the other models. Therefore, ARIMA (1,1,2) model was considered the most suitable model for the price forecasting of sorghum in Ajmer market of Rajasthan.